Marketing Development Through Swot Analysis for Medical Profession Liability Insurance at PT Bumida 1967 - Cicik Harini (Institute of Computer Science (IOCS), 2020)
The purpose of this research is to develop a marketing strategy from PT. BUMIDA 1967, to further develop and increase sales volume. This research was conducted by direct interview method, by filling in some of the questions summarized in the questionnaire to Branch Managers and employees of the marketing division. Data processing method uses SWOT analysis. The results showed that the strategy used by PT. BUMIDA Semarang Branch uses a diversification strategy or an innovation strategy. By using SAP and ETOP analysis, PT. BUMIDA 1967 Semarang Branch is in a strong internal position and an external position on speculative ventures. So the company PT. BUMIDA 1967 Semarang Branch is in an investment position to develop Doctor Liability Insurance products with increasingly aggressive innovations to increase company turnover.